Pattern of Ear Diseases among Paediatric ENT Patient: An Experience from Tertiary Care Centre, Pokhara, Nepal - Sigdel, B; Nepali, R (Journal of Nepal Paediatric Society, 2012)
Introduction: Ear diseases are common in children mainly due to altered anatomy of Eustachian tube which is straighter in children as compared to that in adults. However, the cause of hearing loss in children is more varied, including the etiologies. This study was done to find out the pattern of ear diseases in paediatric age group attending ear, nose and throat OPD in a tertiary care centre in Pokhara, Nepal. Materials and Methods: This is a prospective study done in paediatric patients attending ENT OPD over a period of one year from January 2010 to January 2011. The diagnoses were made on the basis of history and clinical examination. Results were expressed in numbers and percentages. Results: Out of 1632 Pediatric ENT patients, 944 had ear diseases, 59.2% were males and 40.8% females. Wax (33.4%) was the commonest diagnosis followed by Chronic suppurative otitis media (24.3%) and Acute ottitis media (13%). Conclusion: Ear diseases are most common condition in ENT OPD among paediatric age group. Wax, CSOM and ASOM were the three most common ear diseases. J. Nepal Paediatr. Soc. 32(2) 2012 142-145 doi: http://dx.doi.org/10.3126/jnps.v32i2.5673